Allegiance, citizenship and the law the enigma of belonging - Irving, Helen (Elgar studies in legal theory, 2022)
Weaving together theoretical, historical, and legal approaches, this book offers a fresh perspective on the concept of allegiance and its revival in recent times, identifying and contextualising its evolving association with theories of citizenship. The book explores how allegiance was historically owed in return for the sovereign's protection but has been redeployed by modern governments to justify the withdrawal of protection. It examines allegiance from multiple perspectives, including laws for the revocation of citizenship, new ideas of citizenship education, the doctrine of treason, oaths of allegiance, naturalisation tests, and theories of belonging. This thought-provoking book ultimately finds allegiance to be a feudal concept that is inappropriate in the liberal democratic state, and is misplaced, even dangerous, in its association with modern citizenship. Rejecting allegiance, but reaching a constructive resolution, it explores modern alternatives to describe the bond between citizens, advancing a new perspective on the 'enigma' of belonging. With its carefully constructed analysis, this work will prove pivotal in furthering our understanding of allegiance and citizenship. Its legal-theoretical account of a complex and under-theorised concept make it valuable reading for legal and political theorists, legal historians, and scholars of citizenship, law, and social politics" --